2017
DOI: 10.1002/bdra.23562
|View full text |Cite
|
Sign up to set email alerts
|

Update on syphilis and pregnancy

Abstract: While the origins of syphilis remain unknown, it has long been recognized as an infectious entity with complex pathophysiology. In this review, we highlighted the epidemiology and risk factors associated with syphilis. The incidence of syphilis in most populations showed a consistent upward trend until the 1940s with the introduction of penicillin as the preferred treatment. The emergence of congenital syphilis and vertical transmission has been a direct result of heterosexual syphilis transmission. We also ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
20

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 20 publications
(32 reference statements)
1
44
0
20
Order By: Relevance
“…Titer decline varied with maternal disease and treatment. As previously reported, titers usually were higher and declined rapidly in primary and secondary syphilis [10,27]. Accordingly, results showed that women who suffered from stillbirth had a larger proportion of primary and secondary syphilis.…”
Section: General Characteristicssupporting
confidence: 78%
“…Titer decline varied with maternal disease and treatment. As previously reported, titers usually were higher and declined rapidly in primary and secondary syphilis [10,27]. Accordingly, results showed that women who suffered from stillbirth had a larger proportion of primary and secondary syphilis.…”
Section: General Characteristicssupporting
confidence: 78%
“…The main characteristic of primary syphilis is that the skin infection site has a typical chancre, a painless ulceration. Interestingly, in contrast to symptoms caused by other pathogens, chancres can heal spontaneously within a few weeks without treatment . At present, the mechanism of wound healing in syphilis is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in contrast to symptoms caused by other pathogens, chancres can heal spontaneously within a few weeks without treatment. 3 At present, the mechanism of wound healing in syphilis is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A Sífilis Congênita (SC) é decorrente da disseminação do Treponema pallidum, via transplacentária da gestante não tratada ou tratada inadequadamente para o seu concepto em qualquer momento da gestação. A infecção pode causar consequências graves para o concepto, desde sequelas neurológicas até o óbito fetal (1,4) .…”
Section: Introductionunclassified